2022
DOI: 10.1007/s11356-022-22916-x
|View full text |Cite
|
Sign up to set email alerts
|

Leagile and sustainable supplier selection problem in the Industry 4.0 era: a case study of the medical devices using hybrid multi-criteria decision making tool

Abstract: Given the crucial role of the supplier selection problem (SSP) in today’s competitive business environment, the present study investigates the SSP by considering the leagile, sustainability, and Industry 4.0 (I4.0) indicators for the medical devices industry (MDI). In this regard, at the outset, the list of criteria and sub-criteria is provided based on the literature and experts’ opinions. Then, the importance of the indicators is measured utilizing the rough best–worst method (RBWM). In the next step, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 89 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…So far, I4.0 applications have been primarily focused on commercial supply chains, and with this paper, we assert the need for I4.0 frameworks to be engaged in HSCs. For instance, a case study related to the supplier selection process for acquiring medical devices [92] could be studied in the context of HSCs. Non-governmental organizations such as the Red Cross or Médecins Sans Frontières (Doctors Without Borders) [93] can benefit from BDA to predict disease outbreaks and plan their medical SCs.…”
Section: Topical Trends By Yearmentioning
confidence: 99%
“…So far, I4.0 applications have been primarily focused on commercial supply chains, and with this paper, we assert the need for I4.0 frameworks to be engaged in HSCs. For instance, a case study related to the supplier selection process for acquiring medical devices [92] could be studied in the context of HSCs. Non-governmental organizations such as the Red Cross or Médecins Sans Frontières (Doctors Without Borders) [93] can benefit from BDA to predict disease outbreaks and plan their medical SCs.…”
Section: Topical Trends By Yearmentioning
confidence: 99%
“…In a competitive economy environment, the problem of how to determine an appropriate investment allocation of limited resources to select low-risk and high-benefit set of projects is called project portfolio selection (PPS) problem, which is crucial for a/an company/organization (Boyd et al, 2017;ForouzeshNejad, 2023;Kolm et al, 2014). However, risks triggered by multiple uncertainties, such as resource shortages (Afzal et al, 2023;Bai et al, 2020), organizational instability (Mahmoudi et al, 2022), etc., can seriously affect the realization of project benefits, so the problem of PPS considering risks has been widely concerned (Asadabadi & Zwikael, 2021;Hofman et al, 2018;Suresh & Dillibabu, 2020;X.…”
Section: Introductionmentioning
confidence: 99%
“…In his study conducted in 2023, Forouzeshnejad concluded that agility and sustainability are the essential criteria for agility and sustainability in the medical device industry and that flexibility, cost, reliability, smart factory, and quality are crucial criteria determined subsequently [17].…”
Section: Introductionmentioning
confidence: 99%